Handbook of transdisciplinary research - Gertrude Hirsch Hadorn, Holger Hoffmann-Riem, Susette Biber-Klemm, Walter Grossenbacher-Mansuy, Dominique Joye, Christian Pohl, Urs Wiesmann, Elisabeth Zemp (Springer, 2017)
446 p.